Effectiveness of murottal Al-Quran therapy on post-operative pain - Nuzulullail, Agung Subakti; Mustofa, Akhmad; Vranada, Aric (Media Keperawatan Indonesia, 2023)
In the last few decades, non-pharmacological therapy has been commonly used in the management of postoperative pain with the advantage of minimal side effects. Murottal Al-Quran therapy is a non-pharmacological therapy that can be used to treat pain. The application of non-pharmacological murottal Al-Quran therapy for post-operative pain has not yet been clarified. The aim of this literature is to analyze the effect of Al-Quran murottal therapy on patients with post-operative pain. The method used applies the Literature review method. Articles related to the effectiveness of Al-Quran murottal therapy in post-operative pain patients were summarized from the Science Direct and Google Scholar databases. Article searches were carried out using the PRISMA method with keyword searches: post-operative pain, Al-Quran murottal therapy, post and pre-intervention pain scale, and pain scale reduction. As a result of a total of 7 articles identified, women constituted the majority of respondents with an age range of 40-45 years and more than 60 years. The results of the review summarize 1 article using the Al-Kahf letter and 2 articles using the Ar-Rahman letter as a non-pharmacological intervention. Most articles explain that the intervention is implemented for 15 minutes using audio recording media. The Numeric Rating Scale (NRS) is used as a pain scale assessment method. All articles show a decrease in the postoperative pain scale after intervention (NRS pre-post intervention <0.05). In conclusion, Al-Quran murottal therapy is very effective as a non-pharmacological therapy in efforts to reduce the pain scale in post-operative patients.